Análisis de la percepción de violencia de género en la relación de pareja de dos mujeres de San Marcos y dos mujeres de Bogotá, con edades comprendidas entre los 20 y 27 años (2021)
The investigation presents the analysis of the perception of gender violence by 4 women from a large city (Bogotá) and a municipality (San Marcos), who are in a relationship between 20 and 27 years of age.